Comparing ADCP data collected during a seismic survey off the coast of Newfoundland with analysis data from the CONCEPTS operational ocean model. Issue 2 (3rd July 2018) - Zedel, Len; Wang, Yanan; Davidson, Fraser; Xu, Jinshan
ABSTRACT: Oceanographic data collected during seismic surveys have potential to provide a significant resource for oceanographic research. In this paper, acoustic Doppler current profiler (ADCP) data collected during the Chevron 2011 North East Grand Banks survey are analysed. The survey took place in a 32, 000-km 2 area in the North East Grand banks, Orphan Basin region in water depths ranging from 100 to 1500 m and notably, the survey area is crossed by the offshore branch of the Labrador current. Data quality is evaluated by comparing velocities before and after ship turns where we find no significant velocity bias. The ADCP data are compared to data products from the CONCEPTS global ice ocean prediction system operational ocean model. ADCP data and model output agree qualitatively with the model reproducing the long-term fluctuations seen in the data. At higher frequencies between 0.3 and 2.0 cycles/day, the model tends to under-represent the current velocities by about 20%, but the spectral peak associated with inertial oscillations is well resolved. Comparisons of drift track predictions based on the ADCP observations and model output show rms displacement differences of 8 km after 24 h and ∼10 km separations for drift tracks with length under 50 km.